2020
DOI: 10.18043/ncm.81.5.284
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Facilitators and Barriers Among Retired Women in North Carolina

Abstract: R egular physical activity reduces the risk of chronic disease, such as cardiovascular disease, diabetes, and cancer, in later life [1, 2]. However, only half of older North Carolinians (aged 65 or older) meet recommendations for engaging in ≥ 150 min/week of moderate or ≥ 5 min/week of vigorous aerobic activity, or a combination of both [2, 3]. As the population of older North Carolinians grows from 1.6 million to 2.6 million by 2035 [4], community-level efforts to support physical activity in later life will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Marthammuthu et al identified logistical problems in attending exercise programmes as a major barrier for older Malaysian women [ 96 ]. Jones et al highlighted the crucial role of instrumental SOSU in supporting exercise among older retired US-American women [ 94 ], and Arnautovska et al also highlighted its importance in facilitating PA in older Australians [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Marthammuthu et al identified logistical problems in attending exercise programmes as a major barrier for older Malaysian women [ 96 ]. Jones et al highlighted the crucial role of instrumental SOSU in supporting exercise among older retired US-American women [ 94 ], and Arnautovska et al also highlighted its importance in facilitating PA in older Australians [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the commonly reported environmental barriers (i.e., traffic safety, sidewalks, distance and price of the sports centres) in the same age group in the western countries were not mentioned in the current population [ 60 , 61 , 62 , 63 ]. The mentioned environmental barriers were related to COVID-19 and the hot weather.…”
Section: Discussionmentioning
confidence: 99%
“…Resultados de um estudo multicêntrico também evidenciaram que no lazer, as mulheres e pessoas com menor escolaridade e menor renda média per capita são as menos ativas (Chor et al, 2016). As mulheres são menos propensas do que os homens a serem fisicamente ativas e mais propensas a reduzir sua atividade física à medida que envelhecem (Jones, Leeman, & Evenson, 2020).…”
Section: Discussionunclassified